2017
DOI: 10.1155/2017/9868694
|View full text |Cite
|
Sign up to set email alerts
|

Salvia miltiorrhizaRoots against Cardiovascular Disease: Consideration of Herb-Drug Interactions

Abstract: Salvia miltiorrhiza root (Danshen) is widely used in Asia for its cardiovascular benefits and contains both hydrophilic phenolic acids and lipophilic tanshinones, which are believed to be responsible for its therapeutic efficacy. This review summarized the effects of these bioactive components from S. miltiorrhiza roots on pharmacokinetics of comedicated drugs with mechanic insights regarding alterations of protein binding, enzyme activity, and transporter activity based on the published data stemming from bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 77 publications
0
24
0
Order By: Relevance
“…HSYA was shown to inhibit the activity of CYP1A2 and CYP2C11, and to increase the activity of CYP3A1 (Xu et al, 2014). Another report showed that injections that contain Danshen, or other formulations with high levels of tanshinones may lead to Danshen-drug interactions (Chen et al, 2017a). Therefore, if the two combination groups were to be administered separately, different pharmacokinetics may be observed due to altered rates of P450-mediated metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HSYA was shown to inhibit the activity of CYP1A2 and CYP2C11, and to increase the activity of CYP3A1 (Xu et al, 2014). Another report showed that injections that contain Danshen, or other formulations with high levels of tanshinones may lead to Danshen-drug interactions (Chen et al, 2017a). Therefore, if the two combination groups were to be administered separately, different pharmacokinetics may be observed due to altered rates of P450-mediated metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma protein binding rate is associated with drug-drug interactions, which can affect the absorption, distribution, metabolism, and excretion of drugs in vivo (Bohnert and Gan, 2013). According to previous reports, DSS had a low plasma protein binding rate (Zhang et al, 2017a), and HSYA, SAB, and SAA had a high plasma protein binding rate (Jing et al, 2010;Wang et al, 2011;Chen et al, 2017a). Thus, in the process of drug metabolism, the loss rate of SAA, SAB, and HSYA were high.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed to tonify and stabilize kidney Qi and has been widely used for urinary incontinence and frequency. Meanwhile, Dan Shen ( Radix Salviae Miltiorrhizae ) has been used, according to TCM theory, to invigorate the blood and dispel blood stasis, and there have been a lot of reports on this herb in regard to its characteristic effects against cardiovascular disease, 19 , 20 its anti-inflammatory and antioxidant effects, 21 and its chemosensitization effects. 22 In TCM theory, chronic disease is often blamed for blood stasis, and among the CHMs, Dan Shen was the most commonly used herb for dispelling blood stasis.…”
Section: Discussionmentioning
confidence: 99%
“…Salvia miltiorrhiza Bge., called ‘Danshen’ in China, is a well‐known TCM, which was first documented in Shen Nong Ben Cao Jing (Liang et al, ; Shu et al, ). It has been widely used in the clinic for the treatment of various diseases, such as cardiovascular disease (Chen, Li, & Tian, ), cerebrovascular disease (Zeng et al, ), liver fibrosis (Parajuli et al, ) and cancer (Shen, Lou, Zhang, Xu, & Zhang, ). The active components contained in S. miltiorrhiza Bge.…”
Section: Introductionmentioning
confidence: 99%